From The Danube to the Yalu - Clark, Mark W. (Mark Wayne), 1896-1984 (London George G. Harrap and Co. Ltd., 1954)
"From the Danube to the Yalu is General Clark's personal story of his seven years of almost constant struggle with the Communists in the battlefield and at the conference table--a struggle which began when he first came face to face with Soviet duplicity as U.S. High Commissioner for Austria in 1945..."
Include Index, Appendix and Illustration
Keywords: Korean War (1950-1953) -- Clark, Mark W. (Mark Wayne), 1896-1984